ANCIENT AND PRESENT-DAY GLACIENTION OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
Summarizing of study of ancient and recent glaciation of Armenian highland is presented. Reduction of ancient and recent glaciation area of highland from second half of XIX century and strengthening this process at the last twenty years is marked. For the first time four stages of retreat of lateneopleistocene (Wurm) glacier is revealed by typical relief of cirque moraines of Aragats. Supposition about shortly completion of process rise in temperature of climate and start of next fall in temperature – new glacial period is brought.
Keywords: ancient and modern glaciations; radiocarbon dating; cirque moraines of Aragats